Postulation of LR genes in the bread wheat material of Nepal using Indian pathotypes - and S. NAGARAJAN, B.N. MAHTO, S.K. NAYAR* (Indian Phytopathology, 2002)
Forty three bread wheat varieties from Nepal, were evaluated against fifteen pathotypes of Puccinia recondita tritici prevalent in South Asia. Probable leaf rust resistance genes in these lines were postulated. The above wheat lines showed diverse resistance to leaf rust. Genes Lrl, Lr3, Lr9, LrIO, Lr13, Lr23 and Lr26 were identified either singly or in combination in the bread wheat lines. Since central Nepal also serves as the source for the recurrence of leaf rust for the Indo Gangetic plain, use of wheat varieties with diverse resistance would reduce the leaf rust severity and minimise crop losses in the Indo Gangetic plain.